Effects of Ozone Dissolved in Water on the Physicochemical Properties of Activated Carbons Applied in Drinking Water Treatment - Stanisław Biniak; Grzegorz Trykowski; Maciej Pakuła; Andrzej Świątkowski; Zofia Malinowska; Stanisław Popiel (Adsorption Science & Technology)
The results of treating commercial granulated activated carbons with ozone, both gaseous and dissolved in water, were analyzed. The original carbons (Filtrasorb-300 and Carbsorb-38) were carefully flushed with distilled water to remove any water-soluble impurities. For comparison, each of the washed activated carbons was treated separately with aqueous hydrogen peroxide. The following procedures were applied to assess the effects of contact between each carbon and the oxidizing agents: thermogravimetry, alkalimetry, voltammetry, EDX and FT-IR methods to illustrate changes in the surface chemistry, and nitrogen low-temperature adsorption to show up any possible changes in the porous structure. Ozone dissolved in water exhibited the lowest oxidative strength — EDX and FT-IR spectroscopy revealed only a slight oxidation of the Filtrasorb-300 surface layer. Despite its smaller specific area, this carbon surface exhibited greater roughness and was more susceptible to oxidation. The liquid-phase adsorption isotherms of p -chlorophenol from aqueous solution onto this carbon showed that surface oxygen reduced the extent of adsorption. The experimental data were best fitted by the Langmuir isotherm model.